ANALYSIS OF COMPANY VALUE ON COAL SUB SECTOR COMPANIES IN BURSA EFEK INDONESIA - Nurdiyana, Nadya Aisyah; Nur, Dhani Ichsanuddin (Perpustakaan dan Penerbitan Unismuh Makassar, 2021)
The aim of this study was to examine the contribution of liquidity, leverage, and activity on firm value in coal sub-sector companies on the Indonesia Stock Exchange. The sample was taken through purposive sampling so that 20 coal sub-sector companies were obtained. The analytical method used is multiple linear regression analysis. Hypothesis testing is done by using the simultaneous test and partial test. Based on the result, this research claims that liquidity (current ratio) and activity (total asset turnover ratio) cannot contribute to company value, meanwhile, leverage (debt to asset ratio) can contribute to company value.